Sosialisasi Pemilu Damai: Meneguhkan Partisipasi Pemilih Pemula Milenial Dalam Pemilu 2024 - Ulfah, Yetty; Yuni Safitri; Arif Effendi; Ekki Risyad Mauludin (LPPM Universitas HKBP Nommensen, 2024)
This service activity aims to provide socialization on the implementation of 2024 Peaceful Election, which focuses on strengthening the participation of millennial beginner voters in Joyotakan Subdistrict, Surakarta in this five-year Democratic Party. This service activity was carried out in three stages, encompassing preparation, socialization, and evaluation. In the preparation stage, this was done by collecting administrative data from residents of Joyotakan Subdistrict and first-time voters consisting of students from SMK Muhammadiyah 1 Joyotakan. In the socialization stage, it was realized in the form of open seminars held for two (2) days, and in the evaluation stage, it was carried out with the aim of understanding the extent to which this activity has achieved the stated objectives, as well as to identify related strengths, weaknesses, opportunities and threats. The enthusiasm of the seminar participants, especially the first-time millennial voters, is very good in participating in this seminar. Thus, it is hoped that they will have a firm desire to participate in the 2024 Peaceful Elections by both monitoring and properly using their voting rights without being provoked by false news issues.